2021
DOI: 10.3389/fendo.2021.743807
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Adverse Events Associated With SGLT2is: A Meta-Analysis Involving Nine Large Randomized Trials

Abstract: Recently, Lin and colleagues assessed the safety of sodium-glucose cotransporter 2 inhibitors (SGLT2is) by a meta-analysis [1], in which the authors assessed 16 kinds of adverse events (AE) reported in the published articles based on 10 randomized controlled trials. We conducted a further meta-analysis and targeted the association between use of SGLT2is and occurrences of various kinds of serious AE published in the Clinical Trials website (clinicaltrials.gov). Our meta-analysis revealed that use of SGLT2is wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…A possible mechanism was found in their insulin-independent reduction in blood glucose and ensuing hyperglucagonemia [ 139 ]. Similar to the previously discussed UTIs, the earlier studies rejected the apparent increased risk for DKA [ 132 ], while the most recent ones heavily reaffirm the risk [ 82 , 135 , 136 , 140 ].…”
Section: Adverse Effectssupporting
confidence: 55%
See 3 more Smart Citations
“…A possible mechanism was found in their insulin-independent reduction in blood glucose and ensuing hyperglucagonemia [ 139 ]. Similar to the previously discussed UTIs, the earlier studies rejected the apparent increased risk for DKA [ 132 ], while the most recent ones heavily reaffirm the risk [ 82 , 135 , 136 , 140 ].…”
Section: Adverse Effectssupporting
confidence: 55%
“…As previously mentioned, SGLT2i have profound benefits on the cardiovascular system. SGLT2i have been observed to significantly lower the risk of not only renal, but heart failure as well [ 23 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], which is not surprising considering the many effects already discussed in this chapter, such as the improvement of blood pressure, reduction in obesity and promotion of vasodilation, all of which have a beneficial effect on ventricular preload and afterload [ 84 ]. However, the most prominent effects of SGLT2i on heart function are independent of the aforementioned cardiovascular risk factors, which is in fact why they were endorsed in the contemporary heart failure guidelines as Class I recommended therapy [ 90 ].…”
Section: Renoprotective Effects Of Sglt2 Inhibitorsmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, only a small number of studies have investigated the respiratory effects of SGLT2is. Meta-analyses of randomized controlled trials showed that SGLT2is reduce the risk of adverse respiratory events versus placebo, including the risks of respiratory disorders [ 21 ], pneumonia [ 22 ], and respiratory failure [ 23 ], as well as the risk of asthma versus dipeptidyl peptidase-4 inhibitors (DPP4is) [ 24 ]. However, the respiratory effects of SGLT2is compared with other second or third-line antidiabetic drugs remain less well understood, and there is substantial uncertainty regarding the generalizability of trial findings to real-world settings [ 25 ].…”
Section: Introductionmentioning
confidence: 99%